2010
DOI: 10.3109/10428191003728628
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of adult T-cell leukemia–lymphoma and associations with clinical responses to zidovudine and interferon α

Abstract: Adult T-cell leukemia–lymphoma (ATLL) is an HTLV-1-associated lymphoproliferative malignancy that is frequently fatal. We compared gene expression profiles (GEPs) of leukemic specimens from nine patients with ATLL at the time of diagnosis and immediately after combination therapy with zidovudine (AZT) and interferon α (IFNα). GEPs were also related to genetic aberrations determined by comparative genomic hybridization. We identified several genes anomalously over-expressed in the ATLL leukemic cells at the mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…We observed reduced expression of NR4A1 and NR4A3 at mRNA and protein levels in FLII, B-CLL, DLBCL, FLIII, and PMBCL. NR4A1 and NR4A3 mRNA expression was also reduced in publicly available mRNA data sets of global gene expression profiling experiments derived from different B-cell lymphomas [25][26][27][28][29][30][31] in FL and DLBCL, pointing to a tumor suppressive function of both NR4As in certain lymphoma subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…We observed reduced expression of NR4A1 and NR4A3 at mRNA and protein levels in FLII, B-CLL, DLBCL, FLIII, and PMBCL. NR4A1 and NR4A3 mRNA expression was also reduced in publicly available mRNA data sets of global gene expression profiling experiments derived from different B-cell lymphomas [25][26][27][28][29][30][31] in FL and DLBCL, pointing to a tumor suppressive function of both NR4As in certain lymphoma subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…203 (ii) IRF7 is over-expressed in EBV-positive central nervous system lymphomas, 204 as well as in EBV-negative acute lymphocytic leukemia, chronic lymphocytic leukemia, acute myelogenous leukemia, and adult T-cell leukemia/lymphoma. 205,206 (iii) IRF7 induces expression of the EBV principal oncoprotein LMP1 so that they form a regulatory circuit that may potentiate oncogenic effects of both factors. 120 (iv) Moreover, IRF7-expressing NIH 3T3 cells induce tumor formation in nude mice.…”
Section: Functions Of Irf7mentioning
confidence: 99%
“…This approach was followed in a study reported by Alizadeh and colleagues in this issue of Leukemia and Lymphoma [8]. The authors performed gene expression profiling in a series of patients with adult T-cell leukemia at the time of diagnosis and 24 h after treatment initiation with a combination of zidovudine (AZT) and interferon a (IFNa), in order to identify molecular features of the tumor cells in responding versus non-responding patients.…”
Section: Institute Of Pathology University Of Wü Rzburg Germanymentioning
confidence: 99%
“…While some promising results have been reported in ATLL using a combination therapy of AZT and IFNa [13][14][15], these studies do not offer detailed insights into the underlying molecular mechanisms of response to therapy. Alizadeh's study [8] that reports molecular profiling results of ATLL cells investigated before and after combination therapy with AZT and IFNa sheds some light on this issue. Although the number of patients that were included in the study was quite limited, the authors were able to identify specific gene expression signatures that are associated with the responsiveness of the tumor cells to this therapy.…”
Section: Institute Of Pathology University Of Wü Rzburg Germanymentioning
confidence: 99%